Gene Replacement Therapies for Genodermatoses: A Status Quo - Koller, Ulrich; Bauer, Johann W. (Frontiers in Genetics, 2021)
Epidermolysis bullosa (EB) is a genodermatosis, characterized by the formation of extended blisters and lesions on the skin and mucous membranes upon minimal mechanical trauma. The disease is caused by mutations in genes encoding proteins that are essential for skin stability. Functional impairment, reduction, or absence of one of these proteins results in skin fragility due to reduced connectivity between dermis and epidermis. Currently, gene therapy represents the only treatment option with the potential to cure this severe blistering skin disease. Two promising forms of gene therapy are potentially feasible for EB: gene replacement and genome editing. While genome editing for genodermatoses remains at the preclinical stage, gene replacement approaches are clinically advanced and have been applied already to a small number of patients with junctional and dystrophic forms of EB. Here, the viral transduction of the “wild-type” transgene into skin stem cells, followed by autologous grafting of corrected epidermal sheets, led to the regeneration of stable skin. Recent developments regarding designer nuclease-based gene editing strategies enable the establishment of alternative options to restore the gene function in genodermatoses. This is particularly true in cases wherein genetic constellation hinders gene therapy-based gene replacement.